Locutionary and Illocutionary Acts of Prabowo’s First State Address - Tibria Zahira; Hanafi Wibowo; Ellis Tamela (Universitas Pahlawan Tuanku Tambusai, 2026)
Interpreting political speeches requires more than understanding literal meaning; it involves uncovering the speaker’s intended communicative actions. However, studies on Indonesian political speeches remain limited, particularly those integrating both locutionary and illocutionary analysis. This study aims to examine the types and functions of locutionary and illocutionary acts in President Prabowo Subianto’s first state address in 2024. This research employs a qualitative descriptive method with a pragmatic approach. The data were obtained from the official video and transcript of the speech and analyzed using Speech Act Theory proposed by Austin and developed by Searle. The findings reveal 40 locutionary acts (phonetic, phatic, and rhetic) and 137 illocutionary acts (assertive, directive, commissive, expressive, and declarative). Assertive acts are the most dominant, indicating that the speech primarily functions to construct legitimacy, present national conditions, and reinforce credibility. Directive and commissive acts further demonstrate efforts to mobilize public participation and express political commitment.These findings suggest that political speeches operate simultaneously at literal and pragmatic levels, where speech acts function as strategic tools to shape public interpretation and construct leadership identity.